China and the European Union in Africa partners or competitors? - Men, Jing; Barton, Benjamin (Ashgate Pub., 2011)
China's rise on the international scene over the years has correlated with its exponential economic growth. The European Union (EU), has been feeling the heat of Beijing's closer ties with Africa. This book weaves together China and the EU's policy in Africa and the impact of this interaction on Africa's future.